Disaster planning for libraries : process and guidelines - Robertson, Guy, 1890-1960 (Chandos information professional series., 2015)
Libraries are constantly at risk. Every day, many libraries and their collections are damaged by fire, flooding, high winds, power outages, and criminal behaviour. Every library needs a plan to protect its staff, sites and collections, including yours. Disaster Planning for Libraries provides a practical guide to developing a comprehensive plan for any library. Twelve chapters cover essential areas of plan development; these include an overview of the risks faced by libraries, disaster preparedness and responding to disasters, resuming operations after a disaster and assessing damage, declaring disaster and managing a crisis, cleaning up and management after a disaster and normalizing relations, staff training, testing disaster plans, and the in-house planning champion. Provides a practical approach to developing a comprehensive plan for any library, big or smal. lSupplements technical information with interviews and case studiesIncludes appendices ...